Ground surface temperature and humidity, ground temperature cycles and the ice table depths in University Valley, McMurdo Dry Valleys of Antarctica. Issue 11 (8th November 2016) - Fisher, David A.; Lacelle, Denis; Pollard, Wayne; Davila, Alfonso; McKay, Christopher P.
Abstract: In the upper McMurdo Dry Valleys, 90% of the measured ice table depths range from 0 to 80 cm; however, numerical models predict that the ice table is not in equilibrium with current climate conditions and should be deeper than measured. This study explored the effects of boundary conditions (air versus ground surface temperature and humidity), ground temperature cycles, and their diminishing amplitude with depth and advective flows (Darcy flow and wind pumping) on water vapor fluxes in soils and ice table depths using the REGO vapor diffusion model. We conducted a series of numerical experiments that illustrated different hypothetical scenarios and estimated the water vapor flux and ice table depth using the conditions in University Valley, a small high elevation valley. In situ measurements showed that while the mean annual ground surface temperature approximates that in the air, the mean annual ground surface relative humidity (>85%ice ) was significantly higher than in the atmosphere (~50%ice ). When ground surface temperature and humidity were used as boundary conditions, along with damping diurnal and annual temperature cycles within the sandy soil, REGO predicted that measured ice table depths in the valley were in equilibrium with contemporary conditions. Based on model results, a dry soil column can become saturated with ice within centuries. Overall, the results from the new soil data and modeling have implications regarding the factors and boundary conditions that affect the stability of ground ice in cold and hyperarid regions where liquid water is rare. Key Points: Ice table depths in the University Valley consistent with present‐day conditions Ground surface temperature and humidity must be used, not those in the air